Visitor Service Application Using Waterfall method - Haikal, Muhammad; Akbar, Nai’mul (Journal of Computer Science and Informatics Engineering, 2023)
The Center for Human Resources Development and Research in Communication and Information Technology (BBPSDMP KOMINFO) Medan is one of the agencies that has the task of developing human resources and R & D in the fields of work and information and communication technology in border areas. Many guests visit the agency on their duty as a place for human resource development. Currently, the visitor service at this institution is still using the guest book writing system. A new computer-based design system is needed to improve the system. In this study, a visitor service system was designed at the Center for Human Resource Development and Communication and Information Research in Medan using Apache NetBeans IDE 8.0. The research method used in designing this application is the waterfall model method. The purpose of using the waterfall model in designing this application is so that the work process can be carried out in well-structured stages. The results of the problem analysis were obtained from field research in the form of interviews and observations made by representatives of BBPSDMP KOMINFO Medan staff. Taking this into account, the author is interested in making a visitor service application to record visitors who come to the Center for Human Resource Development and Research in Communication and Information Technology, Medan, where this will be useful for increasing the efficiency of working time utilization in receiving visiting guests. Keywords: Application, Waterfall Model, Java, MySQL